PRACTICAL AND LEGAL BASIS OF RETAIL BANKING PRODUCTS LAUNCHING AND SALE - Shakhlo Yunusova (Journal of Artificial Intelligence and Digital Economy, 2024)
This article covers retail banking product introduction and sales services, retail banking product sales strategies, retail loans and non-performing loans, credit policy and credit risk management requirements and research within the topic. In addition, the author has developed conclusions and proposals on the practical and legal basis of the introduction and sale of retail banking products